2011
DOI: 10.1177/1933719111398150
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Progesterone Treatment on Expression of Genes Involved in Uterine Quiescence

Abstract: An important action of progesterone during pregnancy is to maintain the uterus in a quiescent state and thereby prevent preterm labor. The causes of preterm labor are not well understood, so progesterone action on the myometrium can provide clues about the processes that keep the uterus from contracting prematurely. Accordingly, we have carried out Affymetrix GeneChip analysis of progesterone effects on gene expression in immortalized human myometrial cells cultured from a patient near the end of pregnancy. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 140 publications
3
31
0
Order By: Relevance
“…In addition to enhancing the activity of the α-subunit, the β2-subunit inactivates the channel currents by N-type inactivation (Wallner et al, 1999; Xia et al, 2003). Consistent with the idea that β2 inhibits uterine contractility during pregnancy, progesterone (which is high until the end of pregnancy) increases the expression of the BK Ca α-subunit but decreases expression of β2 in MSMCs (Soloff et al, 2011). …”
Section: Extrinsic Mechanisms Of Bkca Channel Modulationsupporting
confidence: 62%
“…In addition to enhancing the activity of the α-subunit, the β2-subunit inactivates the channel currents by N-type inactivation (Wallner et al, 1999; Xia et al, 2003). Consistent with the idea that β2 inhibits uterine contractility during pregnancy, progesterone (which is high until the end of pregnancy) increases the expression of the BK Ca α-subunit but decreases expression of β2 in MSMCs (Soloff et al, 2011). …”
Section: Extrinsic Mechanisms Of Bkca Channel Modulationsupporting
confidence: 62%
“…The addition of RU486 to P4/E2-treated cells led to altered expression transcriptional profiles for 666 genes. Our study revealed genes and pathways related to those identified in previous studies that analyzed the global transcriptomic profiles in pregnant and laboring myometrium in humans and other species (32,53,62,69). The in vitro analysis of transcriptional alterations in hUtSMCs in response to two of the main steroid regulators provides important insights into the role played by a key individual cell type, the smooth muscle cell, in all physiological and pathophysiological states where these two hormones fluctuate.…”
Section: Discussionmentioning
confidence: 84%
“…In uterine smooth muscle cells myocyte enhancer factor 2 is also bound in this complex (57). Previous studies have also reported the upregulation of several transcription factors associated with the transition from pregnant not-in-labor to laboring myometrium in rat, mouse and human (8,16,25,28,32,53,62,69).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Reduction of cell excitability lowers the contraction frequency and leads to uterine quiescence after mid-pregnancy. 35 …”
Section: Proteome-driven Studies On Functional Remodelingmentioning
confidence: 97%